Human Pharmacokinetics and Pharmacodynamics of MF 701 Dermatan Sulfate Administered by Continuous Intravenous Infusion - Agnelli, Giancarlo; Cosmi, Benilde; Renga, Cinzia; Federici, Fiorella; Necil, Giuseppe G; Houin, Georges; Gianese, Francesco (Thrombosis and Haemostasis, 1990)
The pharmacokinetics and haemostatic effects of MF 701 dermatan sulfate (DS) administered by i. v. infusion were studied in 11 healthy volunteers. Each subject received 0.6 mg kg-1 h-1 MF 701 for 10 h. DS plasma concentrations were measured by a chromogenic assay based on the catalysis of thrombin inhibition by HCII. DS plasma levels followed a single compartment pharmacokinetic model, with a half-life of 1.28 ± 0.46 h, a plasma clearance of 2.75 ± 0.46 1/h and a volume of distribution of 4.92 ± 1.36 1 (means ± SD). Steady-state was reached 3 to 6 h after infusion started. The maximal DS plasma concentration was 16.4 ± 5.7 μg/ml. Maximal APTT prolongation over pre-infusion values was 42 ± 7%; TCT performed with bovine and human thrombin was prolonged by 16 ± 7% and 83 ± 35% respectively. No anti-IIa or anti-Xa activities were detected by chromogenic tests. The treatment was well tolerated. The pharmacokinetics of MF 701 infusion are consistent with those previously described after i. v. bolus administration. The infusion of MF 701 allows fast achievement and steady maintenance of elevated DS plasma concentrations.